Differences score between online and offline laboratory sessions of parasitology in Medical Faculty - Atika Widyaningrum; Mega Pandu Arfiyanti; Kanti Ratnaningrum (Qanun Medika - Jurnal Kedokteran FK UMSurabaya, 2023)
Capabilities to diagnose diseases caused by parasites is one of the competencies that must be mastered by general practitioners. This is stated in Standar Kompetensi Dokter Indonesia (SKDI). The branch of parasitology includes protozoa, helminths, and arthropods. Competency can be achieved through debriefing activities and laboratory sessions. During the pandemic, laboratory sessions of parasitology are carried out online with modification of implementation techniques. The study aims to determine the differences in scores between online and offline laboratory sessions of parasitology in medical faculty. Quantitative research used a quasi-experimental method, with a simple random sampling technique. The research data used secondary data scores of laboratory sessions of helminth and protozoa parasitology of Medical students in Universitas Muhammadiyah Semarang (Unimus). Data were analyzed by using a non-parametric Mann-Whitney u-test. From 62 students, there were significant differences in scores between online and offline helminth laboratory sessions (p=0.00) with the average scores of online helminth courses higher than offline laboratory sessions (70.6±19.8). There was no significant difference in grades of online and offline protozoa laboratory sessions (p=0.576) with average scores of online protozoa courses being lower than the offline laboratory session (55.8±25.5). There is a significant difference in scores between the helminth laboratory session of parasitology and there is no difference in scores between the protozoa laboratory session in Medical Faculty.